Physical properties of barley grains at hydration and drying conditions of malt production - Carvalho, Gisandro Reis [UNESP]; Polachini, Tiago Carregari [UNESP]; Augusto, Pedro Esteves Duarte; Telis-Romero, Javier [UNESP]; Bon, José (Wiley, 2021)
Barley has shown several applications in food formulation, mainly after the malting process (hydration, germination, and drying). Because barley is steeped prior the malting, the aim of this work was to determine the physical properties of the grains and their bed as functions of a wide range of moisture content (12.68–80.28% d.b.). Such influences were evaluated and described through mathematical expressions. Length, width, thickness, different diameters, sphericity, and surface area of the barley grains increased with increasing moisture content, up to ~60%. Volume of thousand grains behaved similarly to these properties while their mass was increased continuously with increasing the moisture content. Bulk and true density tended to decrease during hydration while the bed porosity accompanied the density and volume variations. Specific surface area of the grains and bed decreased at higher moisture content due to the grain tri-dimensional expansion during hydration. Polynomial equations could be obtained to predict the studied properties as a function of the moisture content. Both experimental data and resulting models can be used to accurately design equipment and processes involving heat and mass transfer during malting as well as for determining parameters as water diffusion coefficients. Practical applications: Barley is an important cereal food and beverages applications, mainly to malt production. This study evaluated barley properties in a wide range of moisture contents, in order to understand its behavior under hydration and drying conditions. This data will provide important information needed to design different aspects of barley processing and storage. Moisture dependence of physical properties were determined for barley, considering a wide moisture range (12–80%d.b.). Barley achieved an expansion limit in moistures about 60–70% (d.b.). Simple polynomial equations were proposed to represent the physical properties. All physical properties were satisfactorily modeled.